Inflammatory breast cancer: features and outcomes in a breast unit in Dakar, Senegal - Gueye, Mamour; Kane-Gueye, Serigne Modou; Ndiaye-Gueye, Mame Diarra; Gassama, Omar; Diallo, Moussa; Moreau, Jean Charles (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: The aim of this study was to determine clinical features and outcomes of patients with inflammatory breast cancer (IBC) treated in our breast unit. Methods: This study was performed at Gynaecologic and Obstetric Clinic of Dakar Teaching Hospital, in which a breast unit was created since 2007. All women with diagnosis of inflammatory breast cancer in our Breast Unit between January 2010 and December 2013 were included in this study. The diagnosis of IBC was made clinically using the American Joint Committee on Cancer (AJCC) and confirmed histologically. The follow-up cut-off for this data set was December 31st, 2014. All analyses for this study were performed using SPSS software (version 20.0). Results: Between 2010 and 2013, 22 women with breast cancer who met eligibility criteria were included out of 161 patients followed for breast cancer leading to a frequency of 13.6%. The median age at diagnosis was 43.4 years (26-79 years). Mean time to diagnosis was 4 months. The mean time to recurrence was 11.2 months. This recurrence was observed in 45.5% of cases. The median overall survival was 13.3 months (CI 95% 8.576-18.526), the survival rate was 31.8%. Conclusions: This series shows a high frequency of inflammatory breast cancer. These tumours are very aggressive with a very poor prognosis.